1964
DOI: 10.1128/aem.12.4.384-390.1964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Absence of Ciliate Protozoa From the Rumen on Microbial Activity and Growth of Lambs

Abstract: Egypt), AND K. EL-SHAZLY. Effect of absence of ciliate protozoa from the rumen on microbial activity and growth of lambs. Appl. Microbiol. 12:384-390. 1964.-A survey of the components of the rumen ciliate population in a series of adult sheep, raised in the Faculty of Agriculture, University of Alexandria, has shown that a mixture of Entodinium, Isotricha, Ophryoscolex, Diplodinium, and Polyplastron species was found in the rumen contents of Egyptian sheep; no Epidinium and a negligible number of Dasytricha ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
3
4

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 28 publications
5
18
3
4
Order By: Relevance
“…Eine weitere mogliche Ursache fur die grode Streubreite der Resultate verschiedener Defaunierungsversuche sei noch angesprochen. ABOU AKKADA und EL-SHAZLY (1964) sowie OSMAN und Mitarbeiter (1970) wiesen auf unterschiedliche Vorkommen einzelner Protozoenarten bei verschiedenen Tierarten und Erdregionen hin, die mithin auch bei Verfiitterung ahnlicher Rationen zu unterschiedlichen Reaktionen der Kontrolltiere mit intakter Flora fiihren konnten.…”
unclassified
See 1 more Smart Citation
“…Eine weitere mogliche Ursache fur die grode Streubreite der Resultate verschiedener Defaunierungsversuche sei noch angesprochen. ABOU AKKADA und EL-SHAZLY (1964) sowie OSMAN und Mitarbeiter (1970) wiesen auf unterschiedliche Vorkommen einzelner Protozoenarten bei verschiedenen Tierarten und Erdregionen hin, die mithin auch bei Verfiitterung ahnlicher Rationen zu unterschiedlichen Reaktionen der Kontrolltiere mit intakter Flora fiihren konnten.…”
unclassified
“…Dies wurde jedoch auch bei isoliert aufgezogenen Tieren beobachtet (ABOU AKKADA u. EL-SHAZLY, 1964) und liegt an der fehlenden Konkurrenz der Ciliaten. Da die Flagellaten aber nur in einer vergleichsweise geringen Zahl auftreten (2000-30 0001 ml Pansensaft) und vie1 kleiner sind als Ciliaten (HUNGATE, 1966), sind sie keinesfalls in der Lage, die Rolle der Ciliaten zu iibernehmen (BECKER u.…”
unclassified
“…The results of in vivo studies are not consistent with respect to the role of ciliates in fibre degradation [5][6][7][8][9][10]. The experiments described in this study clearly demonstrate that degradations in faunated and defaunated cultures were strongly affected by loading and dilution rates.…”
Section: Discussionmentioning
confidence: 65%
“…For this reason ciliates were considered to be essential to the ruminant, but many in vivo studies have demonstrated that ruminants can survive without a protozoal population present. However, fibre degradation and animal weight gain were usually lower in the absence of ciliates [5][6][7] although no effect or a positive effect of defaunation has been reported as well [8][9][10]. The contradictory results might be attributable to in vivo conditions which are too complex and variable.…”
Section: Introductionmentioning
confidence: 99%
“…The production of SCFA and microbial crude protein based on the degradation of feed constituents accounts for the majority of the nutrients that are utilized by the host animal and these nutrients arise from the diverse microbial activities present in the rumen (Hobson & Wallace, 1982;Hungate, 1966;Prins, 1977;Russell, 1983). In vitro GP, SCFA and ammonium can thus be investigated to study microbial activity (Abou Akkada & El-Shazly, 1964;Van Hoven & Boomker, 1985).…”
Section: Discussionmentioning
confidence: 99%